Analysis of time integration methods for the compressible two-fluid model for pipe flow simulations. (October 2017) - Sanderse, Benjamin; Smith, Ivar Eskerud; Hendrix, Maurice H.W.
Highlights: BDF2 is proposed as time integration method for the two-fluid model. Accuracy and stability are investigated via eigenvalue analysis of the continuous, semi-discrete and fully-discrete equations. A novel automated von Neumann analysis is developed, which does not require symbolic manipulations or source code knowledge. Discrete Flow Pattern Maps are used to determine if the discrete well-posed unstable flow regime matches the theoretical one. Starting from well-posed unstable conditions, the two-fluid model often turns ill-posed before slugs are formed. Abstract: In this paper we analyse different time integration methods for the two-fluid model and propose the BDF2 method as the preferred choice to simulate transient compressible multiphase flow in pipelines. Compared to the prevailing Backward Euler method, the BDF2 scheme has a significantly better accuracy (second order) while retaining the important property of unconditional linear stability ( A -stability). In addition, it is capable of damping unresolved frequencies such as acoustic waves present in the compressible model ( L -stability), opposite to the commonly used Crank–Nicolson method. The stability properties of the two-fluid model and of several discretizations in space and time have been investigated by eigenvalue analysis of the continuous equations, of the semi-discrete equations, and of the fully discrete equations. A method for performing an automatic von Neumann stability analysis is proposed that obtains the growth rate of the discretization methods without requiring symbolic manipulations and that can be applied without detailed knowledge of the source code. The strong performance of BDF2 is illustrated via several test cases related to the Kelvin–Helmholtz instability. A novel concept called Discrete Flow Pattern Map (DFPM) is introduced which describes the effective well-posed unstable flow regime as determined by the discretization method. Backward Euler introduces so much numerical diffusion that the theoretically well-posed unstable regime becomes numerically stable (at practical grid and timestep resolution). BDF2 accurately identifies the stability boundary, and reveals that in the nonlinear regime ill-posedness can occur when starting from well-posed unstable solutions. The well-posed unstable regime obtained in nonlinear simulations is therefore in practice much smaller than the theoretical one, which might severely limit the application of the two-fluid model for simulating the transition from stratified flow to slug flow. This should be taken very seriously into account when interpreting results from any slug-capturing simulations.